Effect of patent ductus arteriosus on pulmonary vascular disease. (27th February 2019) - Philip, Ranjit; Nathaniel Johnson, Jason; Naik, Ronak; Kimura, Dai; Boston, Umar; Chilakala, Sandeep; Hendrickson, Benjamin; Rush Waller, Benjamin; Sathanandam, Shyam
Abstract: The hemodynamic effects of a patent ductus arteriosus (PDA) are well known including systemic hypoperfusion and volume overload on the left ventricle. This article aims to provide a review of the long‐standing effect of a hemodynamically significant PDA on the pulmonary vasculature and the role of cardiac catheterization in preterm infants with a PDA and pulmonary hypertension.